Factors affecting awareness and retention of Ar Rahnu customers: A case of Ar Rahnu YaPEIM in Kedah - Yusriza Helwany, Mt Yusuf (2020)
The establishment of Ar Rahnu YaPEIM has influences a lot to individuals, society as well as to the economic growth of the country. The existence of Ar Rahnu is not only to promote Islamic collateral financing style or for earnings oriented rather to achieve and seek the pleasure of Allah. The numbers of Ar Rahnu branch is reported increasing year by year. In order to raise awareness among the society, optimistic action must be conducted to ensure the success of the organization. This study then attempted to examine the relationship between reputation and religiosity towards the awareness of Ar Rahnu’s customer in Kedah. Quantitative research design is chose in this study where survey is used as the main appliance for gathering data. The sample study contains 350 respondents and the data is analyzed using SPSS version 25 and Smart Partial Least Squares (PLS) method version 3.0. The finding of the study revealed that there are positive/negative relationship towards the awareness and retention of Ar Rahnu’s customer; reputation and religiosity. This research then can improve the performance of Ar Rahnu and any other related body or institute which it can help to develop and conduct relevant program to such parties. This action consequently will contribute to the economic growth. Further study can be conducted within selected industry or business type at larger sample.